Marriage without Parental Blessing from the Perspective of Islamic Family Law - Hendarso, M. Habi; Ja'far, A. Kumedi (Sekolah Tinggi Agama Islam At-Tahdzib Jombang, 2024)
Marriage without parental consent from the perspective of Islamic family law is a complex issue, involving various legal, social, and moral considerations. In Islamic law, parental or guardian consent is essential to ensure the validity of a marriage, and without such consent, a marriage can be considered invalid. The research method used in this study is a qualitative approach, with data collection through in-depth interviews with couples who married without parental consent, as well as interviews with Islamic family law experts and community leaders. The principle of maslahah (benefit) is a reference in protecting the interests of individuals, families, and society. Although Islamic family law provides space for individual freedom in choosing a life partner, it still emphasizes the importance of complying with religious and moral norms. The absence of parental consent can result in serious social and psychological impacts, including conflict within the family, social isolation, and emotional tension. Therefore, this issue needs to be analyzed in depth to understand its implications in the context of law and society.